Reaction Pathways of Methyl Radical and Ethylamine - Huu Tho, Nguyen; Sang, Nguyen Xuan (VNU Journal of Science: Natural Sciences and Technology, 2018)
The mechanisms for the reaction of methyl radical with ethylamine were determined by the density functional theory using the atomic structures of the reactants, transition states and products optimized at the B3LYP/6-311++G(3df,2p) level of theory. Seven transition states were identified for the production of CH 3 CHNH 2 + CH 4 (TS1), CH 3 CH 2 NH + CH 4 (TS2), CH 2 CH 2 NH 2 + CH 4 (TS3), CH 3 CH 2 NHCH 3 + H (TS4), CH 3 CH 2 + CH 3 NH 2 (TS5), C 2 H 6 + CH 2 NH 2 (TS6) and C 3 H 8 + NH 2 (TS7) with the corresponding barriers, 9.34, 9.90, 13.46, 27.70, 39.12, 45.82 and 69.34 kcal/mol. Thermodynamics analysis and potential energy surface show that H-abstraction pathways took place easier than NH 2 -, CH 3 –abstractions, H-substitution of the NH 2 group and CH 3 -substitution in ethylamine. The H-abstraction in methylene group of ethylamine was the most favourable on the PES of this reaction system. Keywords Methyl, Ethylamine, B3LYP, transition states References [1] Lobo, V., et al., Free radicals, antioxidants and functional foods: Impact on human health. Pharmacognosy Reviews, 2010. 4(8): p. 118-126. [2] Phaniendra, A., D.B. Jestadi, and L. Periyasamy, Free Radicals: Properties, Sources, Targets, and Their Implication in Various Diseases. Indian Journal of Clinical Biochemistry, 2015. 30(1): p. 11-26. [3] Slagle, I.R., D. Sarzynski, and D. Gutman, Kinetics of the reaction between methyl radicals and oxygen atoms between 294 and 900 K. The Journal of Physical Chemistry, 1987. 91(16): p. 4375-4379. [4] Rutz L., B.H., Bozzelli J. W., Methyl Radical and Shift Reactions with Aliphatic and Aromatic Hydrocarbons: Thermochemical Properties, Reaction Paths and Kinetic Parameters. American Chemical Society, Division Fuel Chemistry, 2004. 49(1): p. 451-452. [5] Peukert, S.L. and J.V. Michael, High-Temperature Shock Tube and Modeling Studies on the Reactions of Methanol with D-Atoms and CH3-Radicals. The Journal of Physical Chemistry A, 2013. 117(40): p. 10186-10195. [6] Poutsma, M.L., Extension of Structure–Reactivity Correlations for the Hydrogen Abstraction Reaction to the Methyl Radical and Comparison to the Chlorine Atom, Bromine Atom, and Hydroxyl Radical. The Journal of Physical Chemistry A, 2016. 120(26): p. 4447-4454. [7] Shi, J., et al., Kinetic mechanisms of hydrogen abstraction reactions from methanol by methyl, triplet methylene and formyl radicals. Computational and Theoretical Chemistry, 2015. 1074: p. 73-82. [8] Peukert, S.L., et al., Direct Measurements of Rate Constants for the Reactions of CH3 Radicals with C2H6, C2H4, and C2H2 at High Temperatures. The Journal of Physical Chemistry A, 2013. 117(40): p. 10228-10238. [9] Sangwan, M., E.N. Chesnokov, and L.N. Krasnoperov, Reaction CH3 + OH Studied over the 294–714 K Temperature and 1–100 bar Pressure Ranges. The Journal of Physical Chemistry A, 2012. 116(34): p. 8661-8670. [10] Tho, N.H. and N.X. Sang, Theoretical study of the addition and hydrogen abstraction reactions of methyl radical with formaldehyde and hydroxymethylene. Journal of the Serbian Chemical Society, 2018. 83: p. 10. [11] Carl, S.A. and J.N. Crowley, Sequential Two (Blue) Photon Absorption by NO2 in the Presence of H2 as a Source of OH in Pulsed Photolysis Kinetic Studies:  Rate Constants for Reaction of OH with CH3NH2, (CH3)2NH, (CH3)3N, and C2H5NH2 at 295 K. The Journal of Physical Chemistry A, 1998. 102(42): p. 8131-8141. [12] Gray, P. and A. Jones, Methyl radical reactions with ethylamine and deuterated ethylamines. Transactions of the Faraday Society, 1966. 62(0): p. 112-119. [13] Brinton, R.K. and D.H. Volman, Decomposition of Di‐t‐butyl Peroxide and Kinetics of the Gas Phase Reaction of t‐butoxy Radicals in the Presence of Ethylenimine. The Journal of Chemical Physics, 1952. 20(1): p. 25-28. [14] Brinton, R.K., The abstraction of hydrogen atoms from amines and related compounds. Canadian Journal of Chemistry, 1960. 38(8): p. 1339-1345. [15] M. J. Frisch, G.W.T., H. B. Schlegel, G. E. Scuseria, M. A. Robb, J. R. Cheeseman, G. Scalmani, V. Barone, G. A. Petersson, H. Nakatsuji, X. Li, M. Caricato, A. Marenich, J. Bloino, B. G. Janesko, R. Gomperts, B. Mennucci, H. P. Hratchian, J. V. Ortiz, A. F. Izmaylov, J. L. Sonnenberg, D. Williams-Young, F. Ding, F. Lipparini, F. Egidi, J. Goings, B. Peng, A. Petrone, T. Henderson, D. Ranasinghe, V. G. Zakrzewski, J. Gao, N. Rega, G. Zheng, W. Liang, M. Hada, M. Ehara, K. Toyota, R. Fukuda, J. Hasegawa, M. Ishida, T. Nakajima, Y. Honda, O. Kitao, H. Nakai, T. Vreven, K. Throssell, J. A. Montgomery, Jr., J. E. Peralta, F. Ogliaro, M. Bearpark, J. J. Heyd, E. Brothers, K. N. Kudin, V. N. Staroverov, T. Keith, R. Kobayashi, J. Normand, K. Raghavachari, A. Rendell, J. C. Burant, S. S. Iyengar, J. Tomasi, M. Cossi, J. M. Millam, M. Klene, C. Adamo, R. Cammi, J. W. Ochterski, R. L. Martin, K. Morokuma, O. Farkas, J. B. Foresman, and D. J. Fox, Gaussian 09, Revision C.01. Gaussian, Inc., Wallingford CT., 2010. [16] Hatipoglu, A., et al., Photo-oxidative degradation of toluene in aqueous media by hydroxyl radicals. Journal of Photochemistry and Photobiology A: Chemistry, 2010. 215(1): p. 59-68. [17] Eren, B. and Y. Yalcin Gurkan, Possible reaction pathways of the lincomycin molecule according to the DFT calculation method. 2017, 2017. 82(3): p. 11. [18] Becke, A.D., Density‐functional thermochemistry. II. The effect of the Perdew–Wang generalized‐gradient correlation correction. The Journal of Chemical Physics, 1992. 97(12): p. 9173-9177. [19] Becke, A.D., Density‐functional thermochemistry. I. The effect of the exchange‐only gradient correction. The Journal of Chemical Physics, 1992. 96(3): p. 2155-2160. [20] Becke, A.D., Density‐functional thermochemistry. III. The role of exact exchange. The Journal of Chemical Physics, 1993. 98(7): p. 5648-5652. [21] Yang, W., R.G. Parr, and C. Lee, Various functionals for the kinetic energy density of an atom or molecule. Physical Review A, 1986. 34(6): p. 4586-4590. [22] Hehre W. , R.L., Schleyer P. V. R. , and Pople J. A., Ab Initio Molecular Orbital Theory. 1986, New York: Wiley. [23] Andersson, M.P. and P. Uvdal, New Scale Factors for Harmonic Vibrational Frequencies Using the B3LYP Density Functional Method with the Triple-ζ Basis Set 6-311+G(d,p). The Journal of Physical Chemistry A, 2005. 109(12): p. 2937-2941. [24] Herzberg, G., Electronic spectra and electronic structure of polyatomic molecules, 1966, Van Nostrand: New York. [25] Sverdlov L.M., K.M.A., Krainov E. P., Vibrational Spectra of Polyatomic Molecules, 1974, Wiley: New York. [26] Hirota, E., Anharmonic potential function and equilibrium structure of methane. Journal of Molecular Spectroscopy, 1979. 77(2): p. 213-221. [27] Kuchitsu, K., Structure of Free Polyatomic Molecules. 1998: Springer-Verlag Berlin Heidelberg. [28] Hamada, Y., et al., Molecular structural of the gauche and trans conformers of ethylamine as studies by gas electron diffraction. Journal of Molecular Structure, 1986. 146: p. 253-262. [29] Goos, E.B., A.; Ruscic, B., Extended Third Millennium Ideal Gas and Condensed Phase Thermochemical Database for Combustion with Updates from Active Thermochemical Tables. http://garfield.chem.elte.hu/Burcat/burcat.html, March, 2018.